Expressions of IL-12 and its receptors in patients with lumbar disc herniation and their relationship with clinical efficacy - Wang, Xin; Zhou, Shaohuai; Fan, Mingyu; Wang, Ping; Fang, Hongyu; Bian, Feng; Huang, Tao; Du, Xieqin (Cellular and Molecular Biology, 2020)
This study aimed to explore the expressions of interleukin-12 (IL-12) and its receptors IL-23R and IL12RB2 in patients with lumbar disc herniation (LDH) before and after treatment and their relationship with clinical efficacy. A total of 172 LDH patients undergoing surgical treatment in Wuhan Third Hospital, Tongren Hospital of Wuhan University were enrolled as the study group, and 170 healthy subjects as the control group. 5 mL of fasting venous blood was taken before surgery (T0), 1 d (T1), 3 d (T2), 5 d (T3) and 7 d (T4) after treatment respectively. The concentrations of IL-12, IL-23R and IL12RB2 in the two groups were detected, and the correlation between them and the treatment duration and clinical efficacy was analyzed. The study group showed significantly higher serum IL-12, IL-23R and IL12RB2 than the control group before treatment (P < 0.001). In the study group, IL-12, IL-23R and IL-12RB2 were the lowest at T4 (P < 0.001), followed by T3 (P < 0.001). There was no significant difference in IL-23R at T1 and T0 (P > 0.050), and in IL12RB2 at T1 and T2 (P > 0.050). Spearman rank correlation showed that IL-12, IL-23R, IL12RB2 were negatively correlated with treatment duration in the study group (P < 0.001), and were positively correlated with clinical efficacy (P < 0.001). In conclusion, the concentrations of serum IL-12, IL-23R and IL12RB2 in LDH patients are significantly higher than those in normal controls. Moreover, the concentrations are closely related to the rehabilitation of patients and are expected to become therapeutic targets for LDH.